The Role of Biological Sex in Student Evaluation of Influential Educator's Transformational Leadership, Emotional Intelligence, and Charisma - Buntrock, Katie; Gurholt, Zachary; Halverson, James; Kuepers, Paige; Lehman, Anna; Wild, Mariah; Fay, Martha J. (My University, 2016)
Prior research shows a positive correlation between emotional intelligence (EI) and transformational leadership (TL) (Duckett & Macfarlane, 2003) and TL and charisma (Prati, Douglas, Ferris, Ammeter & Buckley, 2003). TL has also been positively correlated with women (Stempel, Rigotti & Mohr, 2015). However, studies have shown that the relationships vary based on sex of the rater. Student perceptions of professors of the same sex have been shown to be more favorable (Levine, Muenchen, & Brooks, 2010). Social learning theory (Bandura, 1977) would suggest that people choose to identify with leaders of the same sex, however it also says that people may identify with a primary caregiver, regardless of gender. This study tests previous findings on variables in perceptions based on sex and examines the role that TL, EI and charisma play in relationships. Results of this study will increase understanding of the role that sex of raters and leaders play in perceptions of leaders’ TL, EI, and charisma.
Color poster with text, images, and graphs.
Keywords: Emotional intelligence; Charisma; Transformational leadership; Comprehensive survey; Biological sex; Posters